Educational status influences cognitive-motor learning in older adults: going to university provides greater protection against aging than going to high school - Voos, Mariana Callil; Piemonte, Maria Elisa Pimentel; Mansur, Letícia Lessa; Caromano, Fátima Aparecida; Brucki, Sonia Maria Dozzi; Valle, Luiz Eduardo Ribeiro do (Arquivos de Neuro-Psiquiatria, 2017)
Objective: To investigate if middle-aged and older adults with a higher education would differ from those with an average education in cognitive-motor tasks involving lower limb function.Methods: A walking version of the Trail Making Test (Walking Executive Function Task, [WEFT]) was used. Eighty volunteers (40: 50–65 years; 40: 66–80 years) were subdivided into average (6–11years of education) and higher education (12–17 years). They received two training sessions (session 1: eight repetitions, session 2: four repetitions), with a one week-interval between them. The Timed Up and Go (TUG) test was performed before and after the training.Results: Volunteers with an average education showed longer times on the WEFT than those with a higher education. Older adults showed lower retention than middle-aged adults (p < 0.001). The TUG was faster after the WEFT training (p < 0.001).Conclusion: The impact of education was observed when locomotion was associated with cognitive tasks. Average education resulted in poorer performance and learning than higher education, mainly in older adults. Gait speed increased after training.
Keywords: cognition; aging; evaluation; executive function; locomotion; visual perception